2012
DOI: 10.1371/journal.pone.0041959
|View full text |Cite
|
Sign up to set email alerts
|

Prion Protein and Shadoo Are Involved in Overlapping Embryonic Pathways and Trophoblastic Development

Abstract: The potential requirement of either the Prion or Shadoo protein for early mouse embryogenesis was recently suggested. However, the current data did not allow to precise the developmental process that was affected in the absence of both proteins and that led to the observed early lethal phenotype. In the present study, using various Prnp transgenic mouse lines and lentiviral vectors expressing shRNAs that target the Shadoo-encoding mRNA, we further demonstrate the specific requirement of at least one of these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 53 publications
0
48
1
Order By: Relevance
“…It is of interest to recall that an early interpretation of the impact of PrP knockout on cerebellar degeneration 30 had to be revisited subsequent to a demonstration of an artifactual effect of certain Prnp null alleles on the adjacent Prnd transcription unit 31 , 32 . However, Mtg 1 transcript levels are reported as being unaltered by shRNA vectors in a follow-up study, 33 tipping the balance to a consideration of off-axis effects of shRNAs against irrelevant genes. Further validation of shRNA knockdown strategies could involve (1) confirming successful knockdown of the Sho protein and (2) genetic rescue of the knockdown effect on protein levels and embryonic development by co-administration of a second vector with the shRNA vector: this second vector would encode a wt Sho protein open reading frame upstream of a heterologous 3'UTR (i.e., a 3' UTR not targeted by the current anti- Sprn shRNAs).…”
Section: Sho Prpc and Embryonic Developmentmentioning
confidence: 99%
“…It is of interest to recall that an early interpretation of the impact of PrP knockout on cerebellar degeneration 30 had to be revisited subsequent to a demonstration of an artifactual effect of certain Prnp null alleles on the adjacent Prnd transcription unit 31 , 32 . However, Mtg 1 transcript levels are reported as being unaltered by shRNA vectors in a follow-up study, 33 tipping the balance to a consideration of off-axis effects of shRNAs against irrelevant genes. Further validation of shRNA knockdown strategies could involve (1) confirming successful knockdown of the Sho protein and (2) genetic rescue of the knockdown effect on protein levels and embryonic development by co-administration of a second vector with the shRNA vector: this second vector would encode a wt Sho protein open reading frame upstream of a heterologous 3'UTR (i.e., a 3' UTR not targeted by the current anti- Sprn shRNAs).…”
Section: Sho Prpc and Embryonic Developmentmentioning
confidence: 99%
“…However, the inactivation of PrP C in zebrafish induced embryonic lethality (Malaga-Trillo & Sempou 2009), highlighting the lack of a clear model that could connect the observations. Recently, it has been reported that this lethal consequence is due to the function of the prion protein family in controlling trophoblastic cell lineage maintenance and differentiation (Passet et al 2012). Several approaches have been employed in this search, from newly designed KO models to cell culture, where PrP C appeared to be involved in oxidative stress , neuroprotection (Li & Harris 2005), copper metabolism (Brown et al 1997), synaptic and nervous transmission (Bremer et al 2010), and cellular adhesion ).…”
Section: Introductionmentioning
confidence: 99%
“…Origin of this lethality was recently found to result from a developmental failure of the trophectoderm-derived compartment 20 . RNA interference is known to potentially induce knockdown of off-targets and thus false phenotypes.…”
Section: Genetic Depletion Of Several Members Of the Prion Protein Famentioning
confidence: 99%
“…However, since it was observed with two independent ShRNAs targeting the Shadoo mRNA, it seems unlikely that this is at the origin of the observed lethality. Furthermore, an attractive alternative hypothesis, that the ShRNA were also targeting the Mtg1 transcript that overlaps the 3′-end of the Shadoo transcript, 16 , 21 could be dismissed by (1) the locations of the ShRNA targeted sequences outside the overlapping region 19 and (2) the absence of differential expression of the Mtg1 transcript in the Shadoo knockdown embryos 20 . Instead, recent data from the literature appear to be in frame with the induced embryonic lethal phenotype and to indirectly comfort this observation.…”
Section: Genetic Depletion Of Several Members Of the Prion Protein Famentioning
confidence: 99%